Crime from the keyboard: organised cybercrime, co-offending, initiation and knowledge transmission - Hutchings, Alice (Crime, law and social change, 2014)
This paper examines a predominantly Australian sample of computer crime offenders involved in fraud and/or unauthorised access. This paper focuses on the extent to which offenders are involved in organised crime, the nature of the relationship between co-offending, initiation and knowledge transmission, and how the online environment facilitates organised crime and co-offending. This qualitative analysis draws from interviews with self-identified offenders, law enforcement officers who investigate these offenses, and court documents, providing a unique understanding of organised crime involving computer systems.